Corrosive oesophagitis in children following ingestion of sodium hydroxide granules--a case report - Janoušek, Petr; Jurovčík, Michal; Kabelka, Zdeněk; Grabec, Pavel (International journal of pediatric otorhinolaryngology, 2005)
Over the past few years, the ENT clinic in Motol has noticed an alarming increase in the number of cases of severe upper GIT injury in children, in the majority of cases caused by accidental ingestion of corrosives. Suicidal and homicidal cases in the paediatric population are rare. The following case study describes an interesting episode involving ingestion of granules of the lye NaOH in 13 children of school age. We furthermore stress the importance of early endoscopic investigation in every patient with possible corrosive injury of the oesophagus. We include a brief description of the diagnostico-therapeutic algorithm applied to each such patient that was developed through interdepartmental research in Motol Faculty Hospital.
Keywords: Esophagus; ezofágus; Male; kaustika; Sodium Hydroxide; chemické popálení; Child; ústa; dítě; Mouth; mužské pohlaví; Esophagoscopy; Caustics; lidé; ezofágoskopie; ženské pohlaví; Humans; Burns, Chemical; hydroxid sodný; Female